Fundamental truths of Biblical peacemaking through courageous conflict resolution - International Christian Mission (U.S.A)
Our families and culture define conflict and the ways we should deal with it. Some of those beliefs are true and helpful but we must know how God wants us to look at conflict and how we should deal with it.
Keywords: Fundamental truths